The possibility of applying the hybrid system to reduce the costs of industrial units (Applied research in the General Company for Textile and Leather Industries / Textile Factory / Hilla) - Jamal Nasser Faisal Al-Shammari; Thaer Sabri Mahmoud Al-Ghabban (Journal of Madenat Alelem University College, 2022)
The purpose of the research is to clarify how to use the hybrid manufacturing system in industrial units through its use of modern production and marketing technology, and to show the impact of using this system on reducing production costs, improving product quality and achieving customer requirements by offering products that meet all his current and future needs, where the problem was research into the dependence of industrial units on traditional production methods, which led to the accumulation of products in warehouses, which is an expensive matter because traditional production systems depend on the method of everything produced is sold, and this opinion does not coincide with the development taking place in the business world and the modern environment. It is necessary to find a new manufacturing system keeping pace with this development and the current competitive world. The research reached several conclusions, the most important of which is that the factory did not use modern methods of production and marketing and relied on the old traditional methods, which led to the production of products that did not meet the needs and requirements of customers and thus led to the accumulation of products in stores and the reluctance of customers to buy them, which led to high costs of these products and their obsolescence. The research reached many recommendations, the most important of which is the necessity of applying the hybrid manufacturing system in the laboratory. To study because of its positive results in improving its performance and reducing its costs significantly as a result of adopting modern methods of production, selling and marketing and adopting the method of withdrawal in production and producing products according to customer requirements, as well as deleting all activities and stages that do not add value to the product.